The Marriage of a Converted Woman with a Religious Leader from Maqashid Syari'ah Perspective at Batu Ampar District - Irfan, Muhamad; Andaryuni, Lilik; Fansuri, Fuad (International Journal on Advanced Science, Education, and Religion, 2025)
The phenomenon of female converts marrying under the guardianship of religious leaders in Batu Ampar District presents a unique issue, as it does not entirely align with national legal procedures, yet enjoys broad acceptance within the local community. While earlier studies have focused on court-appointed guardians (wali hakim) or the role of wali muhakkam in emergencies, limited research has analyzed this phenomenon through the lens of hearing shari'ah. This study seeks to address that gap by exploring the underlying factors, examining the validity of the marriage process according to classical Islamic jurisprudence, and interpreting it through the objectives of Islamic law. Using a qualitative descriptive method, data were collected through interviews and field observations. The findings reveal that the factors prompting the use of religious leaders as marriage guardians include the absence of a Muslim lineage guardian, economic limitations in accessing formal legal procedures, social pressure to maintain family honour, and the high legitimacy of religious leaders within the community. From the perspective of fiqh procedures, the marriage fulfilled all the essential pillars and conditions, such as the presence of acceptance (offer and acceptance), two just witnesses, a guardian (still), and a dowry (mahar). From the viewpoint of maqashid syari’ah, the marriage achieved the protection of religion (hifzh al-din), life (hifzh al-nafs), honor (hifzh al-‘ird), lineage (hifzh al-nasl), and property (hifzh al-mal).